Comparison of Microvascular Decompression and Two Isocenters Gamma Knife for the Treatment of Trigeminal Neuralgia Caused by Vertebrobasilar Dolichoectasia - Zhao, Zhen; Chai, SongShan; Wang, JiaJing; Jiang, XiaoBing; Nie, ChuanSheng; Zhao, HongYang (Frontiers in Neurology, 2021)
Background: Vertebrobasilar dolichoectasia (VBD) is one of the rare causes of trigeminal neuralgia (TN). The common surgical treatments for patients with TN caused by VBD (VBD-TN) are microvascular decompression (MVD) and Gamma Knife radiosurgery (GKRS). However, the therapeutic effects of the two methods have not been clinically compared, so this study was performed to evaluate the treatment outcomes of MVD and GKRS for patients with VBD-TN. Methods: The retrospective study was performed from March 2011 to March 2019 in Wuhan Union Hospital. A total of 80 patients diagnosed with VBD-TN were included in this study, and they were divided into the MVD group (n = 46) and GKRS group (n = 34) according to the surgical methods. The imaging data, intraoperative findings, treatment outcomes, and complications of the two groups were analyzed and compared. Meanwhile, the influencing factors of the treatment effect are also explored on the two groups. Results: Patients who underwent MVD were younger than patients who underwent GKRS (median ages were 61.1 and 65.4 years old, respectively, p = 0.03). The median follow-up was 61.1 months for the MVD group and 56.8 months for the GKRS group. The favorable outcomes [Barrow Neurological Institute (BNI) pain score, BNI scores I–II] occurred in 97.8% of patients treated with MVD and in 78.9% of patients treated with GKRS (p = 0.009). The favorable outcomes in the percentage of patients after MVD 1, 3, 5, and 7 years were 95.7, 85.1, 74.2, and 74.2%, respectively, whereas the corresponding percentages after GKRS were 76.5, 66.2, 56.6, and 47.2%, respectively (p = 0.031). The postoperative complications (except facial numbness) in the MVD group were higher than those in the GKRS group (p = 0.036), but the incidence of new and worsening facial numbness was lower in the GKRS group (p < 0.001). Conclusions: MVD is superior to GKRS in obtaining and maintaining favorable outcomes for patients with VBD-TN, but it also comes with more complications other than facial numbness. Thus, the treatment program can be tailored to a patient's unique condition and wishes.